MULTIPLE RECORDS FROM OSMIUM, NEODYMIUM, AND STRONTIUM ISOTOPE SYSTEMS OF THE NIKUBUCHI ULTRAMAFIC COMPLEX IN THE SAMBAGAWA METAMORPHIC BELT, CENTRAL SHIKOKU, JAPAN - Senda R.; Kachi T.; Tanaka T. (My University, 2006)
The isotopic compositions of Os, Nd, and Sr, as well as major elements of dunites, spinel lherzolites, websterite, and serpentinite from the Nikubuchi ultramafic cumulous complex in the Sambagawa metamorphic belt (SMB) were investigated. The Nikubuchi ultramafic complex is a layered cumulate and is surrounded by a metagabbro massif in the SMB. We obtained a Sm-Nd whole-rock isochron of the Nikubuchi complex with an age of 138 ± 18 (2σ) Ma and an initial 143Nd/144Nd ratio of 0.51270 ± 3. The Nikubuchi complex contains well preserved protogranular textures and cumulous layering structures, and has good correlation coefficients among the major element abundances, which indicate an event before the Sambagawa metamorphism. The εNd values of 138 Ma (+3.5 to +5.3) correspond to the isotope signatures of ocean island basalt (OIB) or island are basalt (IAB), and not mid-ocean ridge basalt (MORB). Taking the results of previous studies into consideration, the most likely origin of the Nikubuchi complex is that of a fragmented block of residual cumulate formed by the OIB magma chamber. The Rb-Sr isotope system has been disturbed by hydration and/or metamorphism after 138 Ma, and the Re-Os isotope system also has no valid isochron. One of the possible causes is that rhenium addition by hydration has occurred subsequent to 60 Ma. The results of the isotope systems show that hydration can cause disturbance in Re-Os systems but not in Sm-Nd systems. This probably reflects differences between these systems in resistance of the host phase. Copyright © 2006 by The Geochemical Society of Japan.
Keywords: CUMULATE COMPLEX; RE-OS ISOTOPE SYSTEM; SAMBAGAWA METAMORPHIC BELT; SM-ND ISOTOPE SYSTEM; ULTRAMAFIC COMPLEX